Strategi Dalam Pembelajaran Bahasa Indonesia Di Sekolah Dasar Daerah Terpencil Nusa Tenggara Timur (NTT) - Rince Jalla Wabang; Lenny Nofriyani Adam (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
Bahasa is one of the important materials taught in Indonesian schools for the important roles in our daily lives. The aim of this study is to determine the effectiveness of learning in a remote island in Flores. The method used is qualitative descriptive with a naturalistic approach and case study. This research was conducted in several places in a remote area on the island of Flores, East Nusa Tenggara. The result shows that Bahasa language learning in the remote area of Flores island is not maximal enough. Primary school teachers are still applying the conventional learning techniques and they do not want to be role models for the teaching-learning process.